Assessment of the Efficacy of L-Lysine Sulfate vis-à-vis L-Lysine Hydrochloride as Sources of Supplemental Lysine in Broiler Chickens - Vijay Bahadur; Sudipto Haldar; Tapan Kumar Ghosh (Veterinary Medicine International)
In this study the effects of L-lysine hydrochloride (containing 78.8% available lysine as crystalline lysine) and L-lysine sulfate (containing 51% available lysine in bacterial cell mass) as source of supplemental lysine in broiler chickens was assessed. The basal diet was supplemented with either L-lysine hydrochloride or L-lysine sulfate to meet lysine requirement. Lysine supplementation irrespective of source improved (𝑃<.05) live weight and food conversion. Live weight and food conversion ratio of the L-lysine sulfate group was superior (𝑃<.05) to the L-lysine hydrochloride group. Supplementation of lysine to the basal diet improved breast meat yield (𝑃<.05). Meat protein content and protein accretion increased (𝑃<.01) when L-lysine sulfate was supplemented. Nutrient metabolizability, N retention, protein utilization efficiency and live weight gain : lysine intake ratio also improved (𝑃<.01) with L-lysine sulfate. A fasting trial conducted after the completion of the feeding trial indicated that the birds receiving L-lysine sulfate retained more of their live weight than the control and the L-lysine hydrochloride dietary groups (𝑃<.05). It was concluded that due to the retained bacterial cell mass, L-lysine sulfate may be a superior source of supplemental lysine than L-lysine hydrochloride for broiler chickens.